Effects of an acidic beverage (Coca-Cola) on absorption of ketoconazole. - Chin, T W (1995)
Absorption of ketoconazole is impaired in patients with achlorhydria. The purpose of this study was to determine the effectiveness of a palatable acidic beverage (Coca-Cola Classic, pH 2.5) in improving the absorption of ketoconazole in the presence of drug-induced achlorhydria. A prospective, randomized, three-way crossover design with a 1-week wash-out period between each treatment was employed. Nine healthy nonsmoking, nonobese volunteers between 22 and 41 years old were studied. Each subject was randomized to receive three treatments: (A) ketoconazole 200-mg tablet with water (control), (B) omeprazole (60 mg) followed by ketoconazole (200 mg) taken with water, and (C) omeprazole (60 mg) followed by ketoconazole (200 mg) taken with 240 ml of Coca-Cola Classic. The pH values of gastric aspirates were checked after omeprazole was administered to confirm attainment of a pH of > 6. Multiple serum samples were obtained for measurements of ketoconazole concentrations by high-pressure liquid chromatography. The mean area under the ketoconazole concentration-time curve from zero to infinity for the control treatment (17.9 +/- 13.1 mg.h/liter) was significantly greater than that for treatment B (3.5 +/- 5.1 mg.h/liter; 16.6% +/- 15.0% of control). The mean peak concentration was highest for the control treatment (4.1 +/- 1.9 micrograms/ml), for which the mean peak concentration showed a significant increase over that for treatment B. The absorption of ketoconazole was reduced in the presence of omeprazole-induced achlorhydria. However, drug absorption was significantly increased, to approximately 65% of the mean for the control treatment, when the drug was taken with an acidic beverage, such as Coca-Cola.